Predisposition of hypersensitivity in patients with exfoliative cheilitis - Luyao Cai; Jiao Wei; Danhua Ma; Hao Xu; Maofeng Qing; Zhen Wang; Yingqiang Shen; Yu Zhou (Elsevier, 2022)
Background/purpose: Exfoliative cheilitis (EC) is a chronic and reversible inflammatory disease of the lips without definite etiology. Clinically, different types of allergens can be found in exfoliative cheilitis patients, however, few studies have focused on the relationship between exfoliative cheilitis and hypersensitivity. This research aimed to investigate the prevalence of hypersensitivity in EC patients. Materials and methods: A prospective study was conducted in 30 patients with exfoliative cheilitis and 30 healthy controls, matched in age and sex. Laboratory tests included serum total IgE, allergen-specific IgE, and food-specific IgG. Results: Increased serum total IgE level, positive food-specific IgG were seen more frequently in exfoliative cheilitis patients than in healthy control (P < 0.05). Special IgE level to FX5 and the degree of food-specific IgG to wheat were seen higher in exfoliative cheilitis patients than in healthy control (P < 0.05). Conclusion: This study suggests that patients with exfoliative cheilitis may have predisposition of hypersensitivity. The detection of allergens should be strengthened in the future clinical work.